In vivo Evaluation of Analgesic, Anti-Inflammatory and Antipyretic Activities of Aqueous Extract from Tamarindus Indica l. Fruit - Md Khalid, Syamimi Md Khalid (2011)
Pharmacological studies were conducted with the aqueous extract of Tamarindus indica L. fruits (TFAE) on experimental animals for evaluating the analgesic, antipyretic, anti-inflammatory activities and to elucidate its mechanism of action. In the analgesic test, three experimental models of nociception used to study the analgesic activity of extract namely, acetic acid-induced abdominal constrictions test and hot-plate test in mice and formalin test in rats. TFAE produced inhibitory effect in all experimental models used. Further study showed that the extract elicited inhibitory activity in both the early and late phases of the formalin test. In addition, TFAE also produced significant inhibition effect (p<0.001) in glutamate and capsaicin-induced paw licking models. Pre-treatment with 5 mg/kg naloxone, a non-selective opioid receptor antagonist, significantly (p<0.001) antagonised the antinociceptive effect of the extract in all tests. This shows the analgesic effect is associated with stimulation of opioid receptors in central brain system. In addition, TFAE also showed anti-inflammatory activity through carrageenan-induced paw edema model and significantly (p<0.001) inhibited inflammation-induced by carrageenan edemogens. In acute chronic inflammation model, Tamarind provoked a significant reduction of both proliferative and transudative phase when tested on cotton pellet-induced granuloma model. At 600mg/kg, TFAE caused maximum inhibition of granuloma with 22.00%. TFAE also elicited antipyretic action when tested in yeast-induced hyperthermia in mice. In the rota rod test, TFAE treated mice did not show any significant motor performance alterations with the dose of 600 mg/kg and this shows that TFAE has no sedative effect. Furthermore, subacute toxicity of 28 consecutive days also shown, there were no deaths or toxic signs recorded in the rats given 1.5, 2.25 and 5.0 g/kg of TFAE.